HUBUNGAN ANTARA PERUBAHAN KADAR HSCRP DENGAN FUNGSI KOGNITIF PADA STROKE ISKEMIK - Betsi Sumanti,* Hexanto,* Widiastuti* (Neurona Majalah Kedokteran Neuro Sains, 2018)
INTRODUCTION THE INCIDENCE OF COGNITIVE IMPAIRMENT IN ACUTE ISCHEMIC STROKE PATIENTS IS INCREASING THE MECHANISM OF THE INFLAMMATORY EFFECT SUCH AS ELEVATED HSCRP LEVEL A NONSPECIFIC INFLAMMATORY MARKER SENSITIVE TO CHRONIC INFLAMMATION DUE TO HYPOPERFUSION AS WELL OTHER VASCULAR RISK IS THOUGHT TO HAVE AN EFFECT ON COGNITIVE FUNCTION